Linewidth of Cyclotron Absorption in Band-Gap Graphene: Relaxation Time Approximation vs. Monte Carlo Method - S.V. Kryuchkov; E.I. Kukhar’; D.V. Zav’yalov (Журнал нано- та електронної фізики)
The power of the elliptically polarized electromagnetic radiation absorbed by band-gap graphene in presence of constant magnetic field is calculated. The linewidth of cyclotron absorption is shown to be non-zero even if the scattering is absent. The calculations are performed analytically with the Boltzmann kinetic equation and confirmed numerically with the Monte Carlo method. The dependence of the linewidth of the cyclotron absorption on temperature applicable for a band-gap graphene in the absence of collisions is determined analytically.